Narrow metal channel inner wall super-smooth structure and preparation method and application thereof
Through high-pressure osmosis reaction etching, the formation of a graded micro-nano rough structure and grafting reactive silicone oil is solved, and the wear resistance and stability of the ultra-slip structure in the inner wall of the narrow channel is insufficient, and the flow resistance is reduced and the fluid delivery efficiency is improved. It is suitable for large-scale Scale application.
Patent Information
- Application Number
- CN202411243798.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The wear resistance and stability of the ultra-slip structure of the existing narrow metal channel inner wall is poor, resulting in poor flow resistance reduction effect, and poor pore uniformity and wear problems in large-scale applications.
High-pressure osmosis reaction etching is used to form a graded micro-nano rough structure, and a stable lubricating layer is formed by modifying the intermediate grafting reactive silicone oil to improve wear resistance and stability.
It significantly reduces flow resistance, improves wear resistance and stability of the inner wall of the channel, is suitable for large-scale applications, and significantly improves fluid delivery efficiency and accuracy in 3D printers, extending the service life of the equipment.
Smart Images

Figure CN119196411A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material surface processing, in particular to super-slip surface technology, and in particular to a super-slip structure of the inner wall of a narrow metal channel, a preparation method thereof and an application thereof. Background Art
[0002] In many applications of high-viscosity fluids, how to effectively reduce the flow resistance of the fluid in narrow channels is a key challenge. Microchannel devices require the fluid to flow smoothly in a small space to ensure efficient operation and precise control of the equipment. However, high-viscosity fluids often encounter greater flow resistance in these narrow channels, resulting in reduced flow, increased pressure, and possible flow instability and blockage problems. This not only affects the performance of the equipment, but may also lead to reduced operating efficiency and shortened service life.
[0003] For example, in the field of direct writing 3D printing technology, the glue extrusion process often involves using air pressure or a rotating screw to provide shear power to extrude a viscous polymer fluid from a tiny nozzle (usually with an inner diameter of 50-400 μm) to form a linear fluid, and the needle movement trajectory is controlled by a computer to form the desired shape structure. However, the highly thixotropic glue used in this process is filled with fillers and has a very high viscosity, usually greater than 400 Pa•s. The extrusion resistance in the narrow needle microchannel is large and the flow rate is small, and problems such as uneven thread thickness, broken threads, and even needle blockage often occur. For this reason, in the field of 3D printing technology, people have proposed solutions such as increasing the shear rate, adding lubricants, or choosing nozzles with larger inner diameters. However, these methods often have their limitations. For example, although increasing the shear rate can reduce the viscosity of the fluid to a certain extent, it will also bring about significant thermal effects, which may cause the polymer fluid to cross-link and solidify prematurely, thus affecting the final use effect; in addition, too high a shear rate will accelerate the wear of the equipment and shorten its service life; adding lubricants (talcum powder, paraffin, fatty acids, fatty acid esters, etc.) to the polymer body will migrate from the inside of the polymer to the tube wall during the extrusion process to form a lubricating layer, increase the wall slip, and reduce the friction resistance of the polymer flow, but the addition of lubricants will reduce the mechanical properties of the polymer body, thereby affecting product performance; although choosing a channel with a larger inner diameter can reduce flow resistance, it will also affect the fine control of the fluid and limit precision applications.
[0004] In addition, in order to solve the problem of flow resistance of highly viscous fluids in narrow channels, people have also proposed solutions of setting up super-slip structures on the inner wall of the channel, such as the patents: CN113819341A A corrosion-resistant super-slip capillary aluminum tube and a preparation method and device thereof; CN112033198A A capillary copper tube for high-speed flow of gallium-based liquid metal containing an oxide layer and a preparation method thereof; WO2021080705A1 Structure and liquid for liquid injection surface structure; CN106865487A Liquid injection type super-slip surface and laser precision micromachining method thereof; CN115928006A A preparation method for quickly constructing a lubrication pipeline, etc. Although the super-slippery structure disclosed in the above patent can effectively solve the problem of flow resistance in narrow channels, during the preparation process of the super-slippery structure in narrow channels, due to the interaction between the channel diameter and the surface tension of the etching liquid, there are problems of uneven etching and difficult to control the etching effect when etching the super-slippery structure, which makes the obtained super-slippery structure have the defect of poor pore uniformity. As a result, the existing super-slippery structure in narrow channels often has problems of poor wear resistance and stability during the application process, which seriously affects the large-scale promotion and application of super-slippery structures in narrow channels. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor wear resistance and stability of existing super-slip structures, and proposes a super-slip structure for the inner wall of a narrow metal channel, a preparation method and an application thereof.
[0006] In order to achieve the above-mentioned invention object, the present invention provides a super-slip structure of the inner wall of a narrow metal channel, including a hierarchical micro-nano rough structure formed on the inner wall of the narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil grafted on the hierarchical micro-nano rough structure by a modified intermediate; Wherein, the narrow metal channel is a metal channel with an inner diameter not greater than 400 μm; The chemical reaction pressure of the high-pressure osmosis reaction is not less than 1 MPa; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size of 1-10 μm and a nano-scale rough structure with a pore size of 10-100 nm; The modified intermediate includes at least one of siloxane, isocyanate, self-polymer and aminosilane; The reactive silicone oil is at least one of amino silicone oil, hydroxy silicone oil, epoxy silicone oil, and hydroxyfluoroether silicone oil.
[0007] The present invention discloses a super-slip structure for the inner wall of a narrow metal channel. The rough structures with different pore sizes formed by etching on the inner wall of the channel by high-pressure penetration reaction not only form an effective synergistic effect, increase the contact surface, and enable the silicone oil to better reside in the rough structure; and under the action of the high-pressure etching reaction, the uniformity of the rough structure is significantly improved, the etching effect is controllable, and the stability and wear resistance of the rough structure in the super-slip structure are significantly enhanced; at the same time, the silicone oil is grafted onto the rough structure by a modified intermediate, which not only makes the silicone oil difficult to lose during the lubrication process, thereby enabling the surface of the rough structure to form a stable flow lubrication layer, but also can improve the grafting effect of the silicone oil and the wear resistance of the lubrication layer through the action of the modified intermediate and the silicone oil, thereby further improving the stability and wear resistance of the super-slip structure. The super-slip structure can significantly reduce the flow resistance in the channel, and has excellent wear resistance and stability, and is suitable for large-scale promotion and application in the treatment of reducing the flow resistance of narrow channels.
[0008] Among them, preferably, the metal is one of aluminum and its alloys, iron and its alloys, copper and its alloys.
[0009] Preferably, the high pressure osmosis reaction is a combination of one or more of high pressure injection, vacuum osmosis, immersion pressurization, and temperature gradient assistance. More preferably, the chemical reaction pressure of the high pressure osmosis reaction is 1-10 MPa.
[0010] Among them, preferably, the pore size of the micron-scale rough structure is 4-8 μm; the preferred pore size can more effectively capture silicone oil and form a stable liquid film, thereby improving the lubrication performance, which is beneficial to improving the wear resistance and stability of the super-slip structure.
[0011] Among them, preferably, the pore size of the nano-scale rough structure is 30-70nm; the preferred pore size can better improve the stability of the surface lubricating layer, reduce the evaporation and loss of silicone oil, and thus help to improve the wear resistance and stability of the super-slip structure.
[0012] Among them, preferably, the porosity of the graded micro-nano rough structure formed by etching the inner wall of the channel is not more than 35%; the larger the porosity, the better the lubricity of the super-lubricant structure, but the worse the wear resistance and stability of the super-lubricant structure; more preferably, the porosity is 25-35%; the preferred porosity can provide sufficient silicone oil storage space while maintaining the mechanical strength and wear resistance of the graded micro-nano rough structure, which is beneficial to improving the lubricity, wear resistance and stability of the super-lubricant structure.
[0013] Among them, preferably, the pore depth of the graded micro-nano rough structure is 10-15 μm; the preferred pore depth helps to improve the storage capacity of silicone oil, while avoiding increased structural brittleness and wear due to too deep pores, thereby helping to improve the wear resistance and stability of the super-slip structure.
[0014] Preferably, the viscosity of the reactive silicone oil is 10-100 mPa•s; the preferred silicone oil viscosity can provide better lubrication performance, is not easy to lose, and can maintain the lubrication effect of the surface for a long time.
[0015] Preferably, the siloxane is at least one of hexamethyldisiloxane, octamethylcyclotetrasiloxane and polydimethylsiloxane. Siloxane can form a dense organic silicon base layer on the metal surface, which is fixed to the metal surface by covalent bonds, giving the surface hydrophobicity and chemical stability, which can effectively enhance the adsorption and retention effect of silicone oil; at the same time, it also has good lipophilicity, which helps to keep the silicone oil evenly attached to the surface, thereby forming a stable lubricating layer.
[0016] Among them, preferably, the isocyanate and the self-polymer are at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, phenyl diisocyanate, tetrafluorophenyl isocyanate, isophorone diisocyanate, adipic acid diisocyanate trimer, isophorone diisocyanate trimer and toluene diisocyanate trimer; the isocyanate group can undergo cross-linking and grafting reaction with reactive silicone oil, which can not only provide more active sites and better reduce the loss of silicone oil, but also has good wear resistance itself and can significantly increase the wear resistance of the lubricating layer. Therefore, the introduction of isocyanate groups has a significant effect on improving the stability and wear resistance of the super-slip structure.
[0017] Among them, preferably, the aminosilane is at least one of aminopropyltriethoxysilane and aminoethylaminoethyltriethoxysilane; aminosilane can increase chemical bonding ability, improve cross-linking reactivity, and enhance interaction with reactive silicone oil.
[0018] Among them, preferably, the modified intermediate is a cross-linked product of siloxane, isocyanate trimer and aminosilane; the preferred modified intermediate has a better effect on enhancing the stability and wear resistance of the super-slip structure.
[0019] In order to achieve the above-mentioned object of the invention, the present invention further provides a method for preparing a super-slip structure on the inner wall of a narrow metal channel, comprising the following steps: (1) performing a first etching treatment on the inner wall of the narrow metal channel by using a high-pressure penetration reaction to construct a micron-scale rough structure on the inner wall of the narrow metal channel; continuing to perform a second etching treatment on the micron-scale rough structure constructed on the inner wall of the narrow metal channel by using a high-pressure penetration reaction to etch a nanometer-scale rough structure in the micron-scale rough structure, thereby forming a hierarchical micro-nano rough structure; (2) After the hierarchical micro-nano rough structure is subjected to hydroxylation treatment, a modified intermediate is grafted to obtain a modified hierarchical micro-nano rough structure; (3) The modified hierarchical micro-nano rough structure is immersed in reactive silicone oil, and after infiltration and grafting reaction, an ultra-smooth structure of the inner wall of the narrow metal channel is obtained.
[0020] Wherein, in step (1), the type of etching solution and etching conditions of the first etching treatment and the second etching treatment are selected and adjusted according to the material of the inner wall of the narrow metal channel; for example, when the inner wall of the metal channel is the inner wall of a stainless steel channel, the etching solution of the first etching treatment can be a mixed aqueous solution of ferric chloride, phosphoric acid and hydrogen peroxide; the mass fraction of ferric chloride is 10-20%, the volume fraction of phosphoric acid is 5-15%, and the volume fraction of hydrogen peroxide is 5-15%; the etching temperature is 35-55°C, and the time is 30-60min. The etching solution of the second etching treatment is a hydrochloric acid solution with a concentration of 0.8-1.2mol / L, the etching temperature is 35-55°C, and the etching time is 1-2h.
[0021] When the metal channel is an aluminum alloy channel, the etching solution of the first etching treatment is a mixed aqueous solution of cupric chloride and hydrochloric acid, the mass fraction of cupric chloride is 5-10 wt%, the mass fraction of hydrochloric acid is 1-5 wt%, the etching temperature is 60-80°C, and the etching time is 50-80min. The etching solution of the second etching treatment is oxalic acid solution, sulfamic acid solution or ammonium persulfate solution; the mass fraction of oxalic acid solution is 1-5%, the mass fraction of sulfamic acid solution is 1-5%, the mass fraction of ammonium sulfate solution is 5-2%, the etching temperature is 30-50°C, and the etching time is 1-1.5h.
[0022] When the metal channel is a copper alloy channel, the etching solution of the first etching treatment is a mixed solution of ammonia water and hydrogen peroxide, wherein the concentration of ammonia water is 1-10 wt%, the concentration of hydrogen peroxide is 3-10 wt%, the etching temperature is 50-70°C, and the etching time is 40-60 min. The etching solution of the second etching treatment is a mixed solution of ammonium fluoride and sulfuric acid, wherein the concentration of ammonium fluoride is 1-5wt%, the concentration of sulfuric acid is 10-30wt%, the etching temperature is 20-50°C, and the etching time is 1-2h.
[0023] Wherein, in step (2), preferably, the hydroxylation treatment method comprises: immersing the hierarchical micro-nano rough structure in a piranha solution; the piranha solution comprises hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of the concentrated sulfuric acid is not less than 70%; the immersion temperature is 50-80°C, and the immersion time is 30-60min.
[0024] Preferably, the grafting method of the modified intermediate comprises: soaking the hierarchical micro-nano rough structure after hydroxylation treatment with a siloxane modification solution, an aminosilane modification solution and / or an isocyanate modification solution respectively.
[0025] Preferably, the siloxane-modified solution comprises a first solvent, siloxane and concentrated sulfuric acid in a mass ratio of 50-150:5-15:1; the first solvent is at least one of ethanol, isopropanol, toluene, p-xylene, tetrahydrofuran, chloroform and n-hexane; and the mass fraction of the concentrated sulfuric acid is not less than 70%.
[0026] Preferably, the immersion temperature of the siloxane-modified solution is 25-45° C., and the soaking time is 2-4 hours.
[0027] Preferably, the volume fraction of the aminosilane-modified solution is 0.5-5%; and the solvent is at least one of water, methanol and ethanol.
[0028] Preferably, the immersion temperature of the aminosilane modified solution is 40-70° C. and the immersion time is 2-4 hours.
[0029] Preferably, the mass fraction of the isocyanate-modified solution is 0.5-2%; the solvent is at least one of methanol, ethanol, toluene, dichloromethane, n-hexane, cyclohexane, and tetrahydrofuran.
[0030] Preferably, the immersion temperature of the isocyanate-modified solution is 25-45° C. and the immersion time is 2-4 hours.
[0031] Among them, in step (3), preferably, the temperature of the infiltration and grafting reaction is 25-60°C, the vacuum degree is lower than 300Pa, and the time is not less than 10h; the preferred infiltration and grafting reaction conditions make the infiltration and grafting cross-linking reaction more thorough, and the lubricity and wear resistance of the super-slip structure are better.
[0032] In order to achieve the above-mentioned purpose of the invention, further, the present invention also provides an application of an ultra-slip structure of the inner wall of a metal channel in a 3D printer; preferably, the ultra-slip structure is used in a 3D printer nozzle; using the ultra-slip structure of the present invention for the nozzle of a 3D printer can significantly reduce the friction between the fluid and the channel wall, thereby reducing the flow resistance, improving the fluid delivery efficiency, and improving the 3D printing accuracy; at the same time, the excellent wear resistance and stability of the ultra-slip structure of the present invention can enable the nozzle to maintain lubricity for a long time, avoiding the rapid wear of the ultra-slip structure of the nozzle during high-intensity use, ensuring the stability of the quality of 3D printed products, reducing the maintenance frequency and replacement cost of equipment, and improving the overall economic benefits.
[0033] Compared with the prior art, the present invention has the following beneficial effects: 1. The rough structures with different pore sizes formed by etching the inner wall of the channel through high-pressure infiltration reaction in the ultra-slip structure of the present invention not only form an effective synergistic effect and increase the contact surface, so that the silicone oil can better reside in the rough structure; but also under the action of high-pressure etching reaction, the uniformity of the rough structure is significantly improved, the etching effect is controllable, and the stability and wear resistance of the rough structure in the ultra-slip structure are significantly enhanced.
[0034] 2. The ultra-lubricous structure of the present invention grafts silicone oil onto the rough structure through a modified intermediate, which not only makes the silicone oil less likely to be lost during the lubrication process, thereby enabling a stable flowing lubrication layer to be formed on the surface of the rough structure, but also enhances the grafting effect of the silicone oil and the wear resistance of the lubrication layer through the action of the modified intermediate and silicone oil, thereby further enhancing the stability and wear resistance of the ultra-lubricous structure.
[0035] 3. The ultra-slip structure of the present invention can significantly reduce the flow resistance in the channel and has excellent wear resistance and stability, and is suitable for large-scale application in the process of reducing the flow resistance in the channel.
[0036] 4. The preparation method of the super-slippery structure of the present invention has simple process, controllable performance, good stability, and is suitable for large-scale production of super-slippery structures.
[0037] 5. The present invention uses a super-slip structure for the nozzle of a 3D printer, which can significantly reduce the friction between the fluid and the channel wall, thereby reducing flow resistance, improving fluid delivery efficiency, and improving 3D printing accuracy, and is suitable for large-scale application in 3D printers. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic diagram of the structure of the ultra-slip structure of the inner wall of a narrow metal channel of the present invention; Figure 2 The diameters of the rubber filaments extruded by the stainless steel nozzle with an inner diameter of 0.15 mm in Example 1 of the present invention and Blank Example 1 at different printing speeds (a is Blank Example 1, b is Example 1).
[0039] Figure numerals: 1-metal tube wall; 2-micrometer-scale roughness structure; 3-nanometer-scale roughness structure; 4-modified intermediate; 5-reactive silicone oil. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.
[0041] Example 1 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm) (e.g. Figure 1including a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (hydroxy silicone oil with a viscosity of 50 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; The modified intermediates include hexamethyldisiloxane, adipic acid diisocyanate trimer, and aminopropyltriethoxysilane; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8 μm and a nano-scale rough structure with a pore size range of 40-50 nm; and the hierarchical micro-nano rough structure has been subjected to siloxane grafting modification treatment; the hierarchical micro-nano rough structure has a porosity of 30% and a pore depth of 12 μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle (ultrasonic cleaning treatment for 10 min in ethanol solution and deionized water respectively, and drying) is subjected to a first etching treatment (the etching solution can be a mixed aqueous solution of ferric chloride, phosphoric acid and hydrogen peroxide; the mass fraction of ferric chloride is 15%, the volume fraction of phosphoric acid is 10%, and the volume fraction of hydrogen peroxide is 10%; the etching reaction pressure is 5 MPa, the temperature is 45°C, and the time is 50 min), and a micron-scale rough structure is constructed on the inner wall of the printer nozzle. After the etching is completed, ultrasonic cleaning is performed in deionized water, isopropanol, and deionized water in sequence, and drying is performed; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is a hydrochloric acid solution with a concentration of 1 mol / L, the etching reaction pressure is 5 MPa, the temperature is 45°C, and the etching time is 1.5 h), and a nano-scale rough structure is formed in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 98%) (temperature 60°C, time 40 min); then the hydroxylated hierarchical micro-nano rough structure was immersed in a siloxane modified solution (isopropanol, hexamethyldisiloxane and concentrated sulfuric acid in a mass ratio of 100:10:1; the mass fraction of concentrated sulfuric acid was 98%) for reaction (350Pa vacuum environment, temperature 35°C, time 10 h), an aminosilane modified solution (2% volume fraction of aminopropyltriethoxysilane in methanol solution) for reaction (temperature 50°C, time 3 h), and an isocyanate modified solution (1% mass fraction of adipic acid diisocyanate trimer in methanol solution) for reaction (temperature 35°C, time 3 h) to obtain the modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 40 °C, vacuum degree 350 Pa, infiltration time 12 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0042] Example 2 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), comprising a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (hydroxy silicone oil with a viscosity of 50 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; Modified intermediates include adipic acid diisocyanate trimer; Among them, the hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8μm and a nano-scale rough structure with a pore size range of 40-50nm; the porosity of the hierarchical micro-nano rough structure is 30% and the pore depth is 12μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle (ultrasonic cleaning treatment for 10 min in ethanol solution and deionized water respectively, and drying) is subjected to a first etching treatment (the etching solution can be a mixed aqueous solution of ferric chloride, phosphoric acid and hydrogen peroxide; the mass fraction of ferric chloride is 15%, the volume fraction of phosphoric acid is 10%, and the volume fraction of hydrogen peroxide is 10%; the etching reaction pressure is 5 MPa, the temperature is 45°C, and the time is 50 min), and a micron-scale rough structure is constructed on the inner wall of the printer nozzle. After the etching is completed, ultrasonic cleaning is performed in deionized water, isopropanol, and deionized water in sequence, and drying is performed; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is a hydrochloric acid solution with a concentration of 1 mol / L, the etching reaction pressure is 5 MPa, the temperature is 45°C, and the etching time is 1.5 h), and a nano-scale rough structure is formed in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 98%) (temperature: 60°C, time: 40 min); then, the hydroxylated hierarchical micro-nano rough structure was immersed in an isocyanate modified solution (methanol solution of adipic acid diisocyanate trimer with a mass fraction of 1%) for reaction (temperature: 35°C, time: 3 h) to obtain a modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 40 °C, vacuum degree 350 Pa, infiltration time 12 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0043] Example 3 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), comprising a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (epoxy silicone oil with a viscosity of 100 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; Modified intermediates include octamethylcyclotetrasiloxane, toluene diisocyanate, aminoethylaminoethyltriethoxysilane; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 1-3 μm and a nano-scale rough structure with a pore size range of 10-30 nm; and the hierarchical micro-nano rough structure has been subjected to siloxane grafting modification treatment; the porosity of the hierarchical micro-nano rough structure is 25%, and the pore depth is 10 μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle is subjected to a first etching treatment (the etching solution can be a mixed aqueous solution of ferric chloride, phosphoric acid and hydrogen peroxide; the mass fraction of ferric chloride is 20%, the volume fraction of phosphoric acid is 15%, and the volume fraction of hydrogen peroxide is 15%; the etching reaction pressure is 1 MPa, the temperature is 35°C, and the time is 30 min), and a micron-scale rough structure is constructed on the inner wall of the metal channel. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropyl alcohol, and deionized water in sequence, and then dried; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is a hydrochloric acid solution with a concentration of 0.8 mol / L, the etching reaction pressure is 1 MPa, the temperature is 55°C, and the etching time is 1 h), and a nanoscale rough structure is formed in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 70%) (temperature 50°C, time 30 min); then the hydroxylated hierarchical micro-nano rough structure was immersed in a siloxane modified solution (ethanol, octamethylcyclotetrasiloxane and concentrated sulfuric acid in a mass ratio of 50:15:1; the mass fraction of concentrated sulfuric acid was 70%) for grafting reaction (temperature 45°C, time 12 h), an aminosilane modified solution (a methanol solution of aminoethylaminoethyltriethoxysilane with a volume fraction of 1%) for reaction (temperature 70°C, time 2 h), and an isocyanate modified solution (a water solution of toluene diisocyanate with a mass fraction of 2%) for reaction (temperature 25°C, time 4 h) to obtain a modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 30 °C, vacuum degree 400 Pa, infiltration time 11 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0044] Example 4 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), comprising a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (amino silicone oil with a viscosity of 10 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; Modified intermediates include toluene diisocyanate trimer, aminoethylaminoethyltriethoxysilane; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 7-10 μm and a nano-scale rough structure with a pore size range of 60-100 nm; and the hierarchical micro-nano rough structure has been subjected to siloxane grafting modification treatment; the porosity of the hierarchical micro-nano rough structure is 35%, and the pore depth is 15 μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle is subjected to a first etching treatment (the etching solution can be a mixed aqueous solution of ferric chloride, phosphoric acid and hydrogen peroxide; the mass fraction of ferric chloride is 20%, the volume fraction of phosphoric acid is 15%, and the volume fraction of hydrogen peroxide is 15%; the etching reaction pressure is 10 MPa, the temperature is 55°C, and the time is 60 min), and a micron-scale rough structure is constructed on the inner wall of the metal channel. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropyl alcohol, and deionized water in sequence, and then dried; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is a hydrochloric acid solution with a concentration of 1.2 mol / L, the etching reaction pressure is 10 MPa, the temperature is 35°C, and the etching time is 2 h), and a nanoscale rough structure is formed in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 85%) (temperature 50°C, time 60 min); then, the hydroxylated hierarchical micro-nano rough structure was reacted with an aminosilane modification solution (3% by volume aminoethylaminoethyltriethoxysilane methanol solution) (temperature 35°C, time 4 h) and an isocyanate modification solution (0.5% by mass aqueous solution of toluene diisocyanate trimer) (temperature 45°C, time 2 h) to obtain a modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 60 °C, vacuum degree 300 Pa, infiltration time 10 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0045] Example 5 A super-slip structure of the inner wall of a metal channel (aluminum alloy 3D printer nozzle with an inner diameter of 0.15 mm), including a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (hydroxy silicone oil with a viscosity of 50 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; The modified intermediates include hexamethyldisiloxane, adipic acid diisocyanate trimer, and aminopropyltriethoxysilane; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8 μm and a nano-scale rough structure with a pore size range of 40-50 nm; and the hierarchical micro-nano rough structure has been subjected to siloxane grafting modification treatment; the hierarchical micro-nano rough structure has a porosity of 30% and a pore depth of 12 μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle (ultrasonic cleaning was performed in ethanol solution and deionized water for 10 min respectively, and then dried) was subjected to the first etching treatment (the etching solution was a mixed solution of copper chloride and hydrochloric acid, the mass fraction of copper chloride was 10 wt%, and the mass fraction of hydrochloric acid was 3.5 wt%; the etching reaction pressure was 5 MPa, the temperature was 70 °C, and the etching time was 60 min), and a micron-scale rough structure was constructed on the inner wall of the printer nozzle. After the etching was completed, it was ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is an oxalic acid solution with a mass fraction of 3.5%; the etching reaction pressure is 5 MPa, the temperature is 40°C, and the etching time is 1.2 h), and a nanoscale rough structure is formed in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 98%) (temperature 60°C, time 40 min); then the hydroxylated hierarchical micro-nano rough structure was immersed in a siloxane modified solution (isopropanol, hexamethyldisiloxane and concentrated sulfuric acid in a mass ratio of 100:10:1; the mass fraction of concentrated sulfuric acid was 98%) for reaction (350Pa vacuum environment, temperature 35°C, time 10 h), an aminosilane modified solution (2% volume fraction of aminopropyltriethoxysilane in methanol solution) for reaction (temperature 50°C, time 3 h), and an isocyanate modified solution (1% mass fraction of adipic acid diisocyanate trimer in methanol solution) for reaction (temperature 35°C, time 3 h) to obtain the modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 40 °C, vacuum degree 350 Pa, infiltration time 12 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0046] Example 6 A super-slip structure of the inner wall of a metal channel (a copper alloy 3D printer nozzle with an inner diameter of 0.15 mm), comprising a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil (hydroxy silicone oil with a viscosity of 50 mPa•s) grafted onto the hierarchical micro-nano rough structure by a modified intermediate; The modified intermediates include hexamethyldisiloxane, adipic acid diisocyanate trimer, and aminopropyltriethoxysilane; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8 μm and a nano-scale rough structure with a pore size range of 40-50 nm; and the hierarchical micro-nano rough structure has been subjected to siloxane grafting modification treatment; the hierarchical micro-nano rough structure has a porosity of 30% and a pore depth of 12 μm; The specific preparation method is as follows: (1) The inner wall of the printer nozzle (ultrasonic cleaning was performed in ethanol solution and deionized water for 10 minutes respectively, and then dried) was subjected to a first etching treatment (the etching solution was a mixed solution of ammonia water and hydrogen peroxide, wherein the concentration of ammonia water was 5wt%, the concentration of hydrogen peroxide was 8wt%, the etching reaction pressure was 5MPa, the temperature was 60°C, and the etching time was 50min), and a micron-scale rough structure was constructed on the inner wall of the printer nozzle. After the etching was completed, the inner wall was ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (2) The micron-scale rough structure constructed on the inner wall of the printer nozzle is subjected to a second etching treatment (the etching solution is a mixed solution of ammonium fluoride and sulfuric acid, the concentration of ammonium fluoride is 3wt%, the concentration of sulfuric acid is 15wt%, the etching reaction pressure is 5MPa, the temperature is 30°C, and the etching time is 1.5h), and a nanoscale rough structure is etched in the micron-scale rough structure to obtain a hierarchical micro-nano rough structure. After the etching is completed, it is ultrasonically cleaned with deionized water, isopropanol, and deionized water in sequence, and then dried; (3) First, the hierarchical micro-nano rough structure was hydroxylated using a piranha solution (hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:1; the mass fraction of concentrated sulfuric acid was 98%) (temperature 60°C, time 40 min); then the hydroxylated hierarchical micro-nano rough structure was immersed in a siloxane modified solution (isopropanol, hexamethyldisiloxane and concentrated sulfuric acid in a mass ratio of 100:10:1; the mass fraction of concentrated sulfuric acid was 98%) for reaction (350Pa vacuum environment, temperature 35°C, time 10 h), an aminosilane modified solution (2% volume fraction of aminopropyltriethoxysilane in methanol solution) for reaction (temperature 50°C, time 3 h), and an isocyanate modified solution (1% mass fraction of adipic acid diisocyanate trimer in methanol solution) for reaction (temperature 35°C, time 3 h) to obtain the modified hierarchical micro-nano rough structure; (4) The modified hierarchical micro-nano rough structure was infiltrated and grafted with reactive silicone oil (temperature 40 °C, vacuum degree 350 Pa, infiltration time 12 h) to obtain an ultra-smooth structure on the inner wall of the metal channel.
[0047] Example 7 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that the etching temperature and time are adjusted so that the porosity of the graded micro-nano rough structure is only 15%. Example 8 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that the etching temperature and time are adjusted so that the porosity of the graded micro-nano rough structure reaches 40%.
[0048] Example 9 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that the etching temperature and time are adjusted so that the pore depth of the graded micro-nano rough structure is only 8 μm.
[0049] Example 10 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: the etching temperature and time are adjusted so that the pore depth of the graded micro-nano rough structure reaches 18 μm.
[0050] Embodiment 11 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that the infiltration oil is hydroxy silicone oil with a viscosity of 5 mPa•s.
[0051] Example 12 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that the infiltration oil is hydroxy silicone oil with a viscosity of 110 mPa•s.
[0052] Example 13 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle), which is different from Example 1 only in that the inner diameter of the stainless steel 3D printer nozzle is 0.4 mm.
[0053] Comparative Example 1 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that dimethyl silicone oil (viscosity 50 mPa•s) is used instead of reactive silicone oil, so the silicone oil is not grafted onto the rough structure.
[0054] Comparative Example 2 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: when performing the etching treatment, no high-pressure infiltration reaction is used, and the etching reaction pressure is only 0.5 MPa.
[0055] Comparative Example 3 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that it is not grafted through an intermediate modifier, but is directly immersed in reactive silicone oil after hydroxylation.
[0056] Comparative Example 4 A super-slip structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle), which is different from Example 1 only in that the inner diameter of the stainless steel 3D printer nozzle is 0.5 mm.
[0057] Comparative Example 5 A super-slip structure of the inner wall of a metal channel, which is different from Example 1 only in that the inner diameter of the stainless steel 3D printer nozzle is 0.5 mm, and when etching, high-pressure infiltration reaction is not used, and the etching reaction pressure is only 0.5 MPa.
[0058] Comparative Example 6 A super-slip structure of the inner wall of a metal channel, which is different from Example 1 only in that the inner diameter of the stainless steel 3D printer nozzle is 0.4 mm, and when etching, high-pressure penetration reaction is not used, and the etching reaction pressure is only 0.5 MPa.
[0059] Comparative Example 7 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: the etching temperature and time are adjusted so that the graded micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8 μm and a nano-scale rough structure with a pore size range of 120-150 nm.
[0060] Comparative Example 8 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: the etching temperature and time are adjusted so that the graded micro-nano rough structure includes a micron-scale rough structure with a pore size range of 12-15 μm and a nano-scale rough structure with a pore size range of 40-50 nm.
[0061] Comparative Example 9 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: the etching temperature and time are adjusted so that the graded micro-nano rough structure includes a micron-scale rough structure with a pore size range of 0.5-0.8 μm and a nano-scale rough structure with a pore size range of 40-50 nm.
[0062] Comparative Example 10 A super-smooth structure of the inner wall of a metal channel (a stainless steel 3D printer nozzle with an inner diameter of 0.15 mm), which is different from Example 1 only in that: the etching temperature and time are adjusted so that the graded micro-nano rough structure includes a micron-scale rough structure with a pore size range of 5-8 μm and a nano-scale rough structure with a pore size range of 6-8 nm.
[0063] Blank example 1 A stainless steel 3D printer nozzle with an inner diameter of 0.15 mm, without any treatment.
[0064] Blank example 2 Aluminum alloy 3D printer nozzle with an inner diameter of 0.15mm without any treatment.
[0065] Blank example 3 Copper alloy 3D printer nozzle with an inner diameter of 0.15 mm without any treatment.
[0066] Blank example 4 A stainless steel 3D printer nozzle with an inner diameter of 0.5 mm, without any treatment.
[0067] Experimental example: The 3D printer nozzles in the above-mentioned Examples 1-13, Comparative Examples 1-10 and Blank Examples 1-4 were subjected to direct writing 3D printing glue extrusion test (5 tests per group, taking the average value): at an air pressure of 60psi and a screw speed of 138r / min, 1700SE silicone rubber, 1700SE silicone rubber with 5wt% silica nanoparticles added, and 1700SE silicone rubber with 10wt% silica nanoparticles added were used as printing slurries for printing tests, and the glue extrusion flow rate, stable lubrication duration, and nozzle clogging of each 3D printer nozzle were measured. The experimental results are as follows: The results of the experimental example show that: From the analysis of the experimental data of the embodiments, comparative examples and blank examples, it can be seen that the liquid-like super-slippery surface structure of the microporous structure of the inner wall of the channel provided by the present invention can effectively reduce the friction between the inner wall of the needle and the high-viscosity fluid, while significantly improving the wear resistance of the super-slippery surface structure, thereby greatly extending the lubrication duration. Among them, the pore size, pore depth, porosity, silicone oil type, whether the intermediate modifier is grafted and the etching reaction pressure of the rough structure in the super-slippery structure have a relatively significant effect on the lubrication performance and wear resistance of the super-slippery structure. From the analysis of the experimental data of Example 1 and Comparative Example 1, it can be seen that the grafting of silicone oil onto the hierarchical micro-nano rough structure can significantly improve the wear resistance of the super-slip structure, and its wear resistance is significantly improved compared with the existing form of directly loading silicone oil (Comparative Example 1); from the analysis of the experimental data of Example 1 and Comparative Example 2, it can be seen that when etching to generate the hierarchical micro-nano rough structure, the use of high-pressure infiltration reaction can significantly improve the uniformity of the rough structure, thereby significantly improving its wear resistance; from the analysis of the experimental data of Example 1 and Comparative Example 3, it can be seen that the grafting of the intermediate modifier onto the hierarchical micro-nano rough structure can increase the grafting effect of silicone oil and improve the wear resistance of the super-slip layer, which significantly improves the wear resistance of the super-slip structure; from the analysis of the experimental data of Examples 1, 13, Comparative Examples 4-6 and Blank Example 4, it can be seen , the high-pressure penetration reaction can only significantly improve the uniformity of the rough structure of narrow channels (not greater than 0.4μm), while for channels with larger diameters, the improvement in wear resistance is not obvious; analysis of the data of Example 1 and Examples 11-12 shows that the viscosity of the reactive silicone oil also affects the wear resistance of the super-lubricating structure. When the viscosity of the infiltration oil is 10-100mPa.s, the super-lubricating structure has better wear resistance; analysis of the data of Example 1 and Comparative Examples 7-8 shows that in the super-lubricating structure, the pore size of the nano-rough structure and the micron-rough structure has a significant effect on the wear resistance of the super-lubricating structure. The smaller micron pore size (1-10µm) can more effectively capture the infiltration oil and form a stable liquid film, thereby improving the lubrication performance; the nano-scale pore size (10-100 The results of Example 1 and Example 9-10 show that a moderate pore depth (10-15 µm) can further improve the stability of the surface lubricating layer and reduce the evaporation and loss of the impregnating oil. The analysis of the data of Example 1 and Example 9-10 shows that a moderate pore depth (10-15 µm) helps to improve the storage capacity of the impregnating oil while avoiding increased structural brittleness and wear due to too deep pores. The analysis of the data of Example 1 and Example 9-10 shows that a moderate porosity (25%-35%) can provide sufficient storage space for the impregnating oil while maintaining the mechanical strength and wear resistance of the structure.In addition, analysis of the data of Example 1, Examples 5-6 and Blank Examples 1-3 shows that the liquid-like super-slip surface structure of the microporous structure of the inner wall of the channel provided by the present invention effectively reduces the friction between the inner wall of the nozzle and the high-viscosity fluid, and the wall-slip drag reduction effect is very significant; under the same printing parameters, the glue extrusion flow rate of the nozzle with the super-slip structure of the present invention is 2-3 times that of the unmodified needle; the maximum printing speed adapted is about 1-2 times that of the unmodified nozzle, and it is also found during the experiment that the glue wire of the nozzle without the super-slip modification breaks on the substrate during high-speed printing, and the wire of the nozzle with the super-slip structure of the present invention remains straight and intact when printing at a higher speed (see. Figure 2 ); in particular, by arranging the super-slip structure of the present invention in the nozzle, it is possible to obtain a thinner silk thread when the nozzle moves at a high speed, and the printable rubber wire diameter is also much smaller than the rubber wire diameter printed by the nozzle needle. It can be seen that the use of the super-slip structure of the present invention in a 3D printer can significantly reduce the friction between the fluid and the channel wall, thereby reducing the flow resistance, improving the fluid delivery efficiency, and improving the 3D printing accuracy; at the same time, the excellent wear resistance and stability of the super-slip structure of the present invention can enable the nozzle to maintain lubricity for a long time, avoiding the rapid wear of the super-slip structure of the nozzle during high-intensity use, ensuring the stability of the quality of 3D printed products, reducing the maintenance frequency and replacement cost of the equipment, and improving the overall economic benefits.
[0068] For those skilled in the art, various other corresponding changes and modifications can be made according to the technical solutions and concepts described above, and all of these changes and modifications should fall within the protection scope of the claims of the present invention.
Claims
1. A super-slip structure on the inner wall of a narrow metal channel, characterized in that: It includes a hierarchical micro-nano rough structure formed on the inner wall of a narrow metal channel by high-pressure infiltration reaction etching, and a reactive silicone oil grafted on the hierarchical micro-nano rough structure by a modified intermediate; Wherein, the narrow metal channel is a metal channel with an inner diameter not greater than 400 μm; The chemical reaction pressure of the high-pressure osmosis reaction is not less than 1 MPa; The hierarchical micro-nano rough structure includes a micron-scale rough structure with a pore size of 1-10 μm and a nano-scale rough structure with a pore size of 10-100 nm; The modified intermediate includes at least one of siloxane, isocyanate, self-polymer and aminosilane; The reactive silicone oil is at least one of amino silicone oil, hydroxy silicone oil, epoxy silicone oil, and hydroxyfluoroether silicone oil.
2. The super-slip structure according to claim 1, characterized in that: The porosity of the hierarchical micro-nano rough structure formed by etching the inner wall of the channel is no more than 35%.
3. The super-slip structure according to claim 1, characterized in that: The pore depth of the hierarchical micro-nano rough structure is 10-15 μm.
4. The super-slip structure according to claim 1, characterized in that: The chemical reaction pressure of the high-pressure osmosis reaction is 1-10 MPa.
5. The super-slip structure according to claim 1, characterized in that: The reactive silicone oil has a viscosity of 10-100 mPa•s.
6. The super-slip structure according to claim 1, characterized in that: The siloxane is at least one of hexamethyldisiloxane, octamethylcyclotetrasiloxane and polydimethylsiloxane.
7. The super-slip structure according to claim 1, characterized in that: The isocyanate and the self-polymer are at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, phenyl diisocyanate, tetrafluorophenyl isocyanate, isophorone diisocyanate, adipic acid diisocyanate trimer, isophorone diisocyanate trimer and toluene diisocyanate trimer.
8. The super-slip structure according to claim 1, characterized in that: The aminosilane is at least one of aminopropyltriethoxysilane and aminoethylaminoethyltriethoxysilane.
9. A method for preparing the super-slip structure according to any one of claims 1 to 8, characterized in that: (1) performing a first etching treatment on the inner wall of the narrow metal channel by using a high-pressure penetration reaction to construct a micron-scale rough structure on the inner wall of the narrow metal channel; continuing to perform a second etching treatment on the micron-scale rough structure constructed on the inner wall of the narrow metal channel by using a high-pressure penetration reaction to etch a nanometer-scale rough structure in the micron-scale rough structure, thereby forming a hierarchical micro-nano rough structure; (2) After the hierarchical micro-nano rough structure is subjected to hydroxylation treatment, a modified intermediate is grafted to obtain a modified hierarchical micro-nano rough structure; (3) The modified hierarchical micro-nano rough structure is immersed in reactive silicone oil, and after infiltration and grafting reaction, an ultra-smooth structure of the inner wall of the narrow metal channel is obtained.
10. An application of the super-slip structure according to any one of claims 1 to 8, characterized in that: Application in 3D printers.
Citation Information
Patent Citations
Preparation method of super-hydrophobic coating layer on aluminum surface
CN105521934A
Integrated spray printing device used for additive and subtractive manufacturing
CN107199693A
Method for applying material with regular bulge array and sliding surface to water mist collection
CN112095098A
Titanium-based alloy with bionic super-smooth surface structure and preparation method and application of titanium-based alloy
CN113481564A
Anti-corrosion super-smooth capillary aluminum pipe and preparation method and device thereof
CN113819341A
